INFLUENCE OF INTERNAL CONTROL AND FINANCIAL HARDSHIP ON EARNINGS MANAGEMENT: CEO REPUTATION AS A MODERATOR IN INDONESIAN PUBLIC COMPANIES - Dewi , Rina Sari (Ayden International Journal of Banking, Finance and Technology, 2024)
This research examines the effect of internal control and financial distress on earnings management and how CEO reputation moderates this relationship in Indonesian listed companies between 2019 and 2020. The sample was selected using purposive sampling, and panel regression analysis was conducted using SmartPLS software. The study employed the accrual earnings management approach to measure earnings management, the Springate model to measure financial distress, the internal control index to measure internal control, and the CEO’s reputation index to measure CEO reputation. The findings show that both financial distress and internal control have a positive effect on earnings management. Additionally, the results suggest that CEO reputation has a moderately significant and positive effect on the relationship between financial distress and earnings management. The research provides valuable insights for corporate governance and investment strategies, highlighting the importance of internal control and CEO reputation in decisionmaking processes. The novelty of this study lies in the investigation of how CEO reputation moderates the relationship between financial distress and earnings management, contributing to the literature on corporate governance and financial management.